Paradigma Nusantara Methodology Variety: Re-embedding Nusantara Values into Research Tools - Ari Kamayanti (International Journal of Religious and Cultural Studies, 2021)
This article aims to offer an approach to derive Nusantara values into research methodology. Through substantive tenets (kaidah substantif) proposed by Mulawarman, methodology to construct variety of methods are put forward. There are three steps that must be taken to ensure that Paradigma Nusantara's tenets can become integral with research results, thus producing new or renewed Nusantara science. Paradigma Nusantara methodology will ensure that knowledge will be built upon strongly-believed values which cater creativity and freedom that will lead to decolonization of science. Examples of Paradigma Nusantara methodologies, both which have been executed and can be considered to be put to use are proposed in this article.